Focus on histological abnormalities of intrahepatic vasculature in chronic viral hepatitis. (6th March 2018) - Guido, Maria; Sarcognato, Samantha; Russo, Francesco P.; Cardin, Romilda; Piciocchi, Marika; Colloredo, Guido; Farinati, Fabio
Abstract: Background & Aims: The histological intrahepatic microvasculature lesions have not been deeply investigated outside the setting of portal hypertension. The aim of this study was to analyse the type and the prevalence of microvasculature abnormalities and their correlation with inflammatory activity, fibrosis stage and tissue markers of fibrogenesis, angiogenesis and oxidative DNA damage in liver biopsies obtained from patients with chronic viral hepatitis. Methods: Seventy‐four liver biopsies from untreated patients affected by hepatitis B (22 cases) and C (52 cases) were included. The presence of microvascular changes was correlated with (i) the severity of the activity and fibrosis; (ii) immunohistochemical markers of angiogenesis (CD34) and hepatic stellate cells activation (alpha‐smooth muscle actin); (iii) a tissue marker of oxidative damage (8‐OHdG adducts). Results: Sixty‐five out of 74 biopsies (87.8%) showed vascular lesions. Portal angiomatosis was the most prevalent (62.2%) and it was associated with, on 1 side, the fibrosis stage at both univariate ( P  < .0001) and multivariate analysis ( P  = .01, OR = 9.4 [1.6‐54]) and, on the other, with angiogenesis ( P  = .05) and hepatic stellate cells activation ( P  = .002). Interestingly, 36/46 cases with portal angiomatosis were at early/intermediate fibrosis stage. The hepatic stellate cells activation was also associated with the presence of aberrant periportal vessels ( P  = .01). Conclusions: The histological alterations of intrahepatic microvasculature, usually seen in cirrhosis and portal hypertension, occur in chronic viral hepatitis even at early/intermediate fibrosis stages. Their correlation with angiogenesis and fibrogenesis supports a possible involvement in disease progression.